1997
DOI: 10.1002/eji.1830270808
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of the BV17 element in nickel‐specific human T cell receptors relates to severity of contact sensitivity

Abstract: Hypersensitivity to nickel (Ni) represents the most common manifestation of contact allergy in humans. The role of metal-specific T cells in this disease is well established, but the molecular interactions involved in their activation are poorly understood. We examined the T cell receptor (TCR) repertoire in T cells activated with either NiSO4 or NiSO4-treated human serum albumin from six allergic patients. For the three most hyperreactive donors, we found a strong over-representation of the TCR BV17 element. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 41 publications
6
61
0
Order By: Relevance
“…Previous studies from our laboratory have already shown that human Ni-reactive T cell clones could indeed be induced by Ni 2ϩ complexed to HSA (HSA-Ni) (5,20). Subsequently, similar data have been reported by Artik et al (21) for murine T cells.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies from our laboratory have already shown that human Ni-reactive T cell clones could indeed be induced by Ni 2ϩ complexed to HSA (HSA-Ni) (5,20). Subsequently, similar data have been reported by Artik et al (21) for murine T cells.…”
supporting
confidence: 78%
“…Human hypersensitivity to Ni, like contact allergies in animal models, is mediated by allergen-specific T cells (1,2,20). HLArestricted Ni-reactive T cell lines and clones of both CD4 and CD8 phenotypes have repeatedly been isolated by NiSO 4 or NiCl 2 stimulation of T cells from peripheral blood or skin lesions of allergic patients and even from nonsensitized individuals (1,9,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we and others have shown that the human Tcell clone ANi2.3, isolated from a patient with nickel hypersensitivity, reacts with Ni ++ presented by the human MHCII protein DR52c bearing an unknown peptide (17,18). Our efforts to find this peptide among the peptides naturally processed and bound to DR52c failed, suggesting that it may be present in very low abundance.…”
Section: Resultsmentioning
confidence: 87%
“…These primers also included restriction sites to permit insertion of the amplified fragments into a TCR ␤-chain expression vector, pHBAcPrMC␤2, adjacent to murine C␤2 or a TCR ␣-chain expression vector, pSFFMC␣, adjacent to murine C␣ (E. Boen, A. Crownover, M. McIlhaney, A. Korman, and J.B., unpublished results). The chimeric TCR genes were introduced into the TCR-negative and human CD4-expressing T cell hybridoma 54 by electroporation as described (24). Transfectants were screened for surface expression of TCR and verified to be functional as determined by release of IL-2 after stimulation with an appropriate V␤-selective superantigen presented by autologous Epstein-Barr virus-transformed B cells.…”
Section: Methodsmentioning
confidence: 99%